Cartografia Simbólica: Configuração Religiosa no Espaço Urbano de João Pessoa (PB) - Lemos, Niedja de Almeida Brito (2010)
The urban space is represented by the multiplicity of images, which can be observed as from the diversified panorama of the views, typical of contemporaneousness, among which the one produced by the religious dynamics. In this sense, this research aimed at mapping aspects of the religious phenomenon in the city of João Pessoa (PB) as from the configuration of its symbolic effects in the urban space. The methodology used is the identification and the analysis of the implantation of religious practice places, utilizing resources made available by Geoprocessing Techniques, combining Technological Sciences with the space analysis methodology built up within the Social Sciences, throughout the elaboration of symbolic cartography. As a result of the research, we produced thematic maps of distribution of the religious practice spaces in the city of João Pessoa and the borough with concentration of such spaces. Based upon the systematic observation and participation in practices within the Evangelical Church God s Assembly/missions, the space chosen to accomplish the symbolic cartography, we identify an internal dynamics around the doctrinal precepts creating a web of social relationships, the mapping of which designs trajectories configuring a religious parameter within the city.